Realization of quasicrystalline quadrupole topological insulators in electrical circuits - Bo Lv (Nature Portfolio, 2021)
Higher order topological systems add an additional layer of complexity to the bulk boundary correspondence by being able to sustain additional modes such as corner and hinge states. Here, the authors use electrical circuits to realize a two-dimensional quasicrystalline quadrupole topological insulator without discrete translational symmetry and observe localized corner modes.